Pulmonary function in patients with acute coronary syndrome treated with ticagrelor or clopidogrel (from the Platelet inhibition and Patient Outcomes [PLATO] pulmonary function substudy) - Storey, Robert; Becker, Richard C.; Harrington, Robert A.; Husted, Steen; James, Stefan K.; Cools, Frank; Steg, Philippe Gabriel; Khurmi, Nardev S.; Emanuelsson, Hakan; Lim, Soo Teik; Cannon, Christopher P.; Katus, Hugo; et al. (The American journal of cardiology, 2011)
The Platelet Inhibition and Patient Outcomes (PLATO) trial showed that ticagrelor reduced the risk for cardiovascular events in patients with acute coronary syndromes compared to clopidogrel but was associated with increased incidence of dyspnea. This substudy assessed whether ticagrelor affects pulmonary function in patients with acute coronary syndromes: 199 patients enrolled in the PLATO trial and receiving randomized treatment with ticagrelor 90 mg twice daily (n = 101) or clopidogrel 75 mg/day (n = 98) took part in the pulmonary function substudy. Patients with advanced lung disease, congestive heart failure, or coronary artery bypass graft surgery after the index event were excluded. Pulse oximetry (blood oxygen saturation), spirometry (forced expiratory volume in 1 second, forced vital capacity, and forced expiratory flow between 25% and 75% of forced vital capacity before and 20 minutes after inhalation of a β2 agonist), lung volumes (total lung capacity, functional residual capacity, residual volume), and diffusion capacity were performed after patients received study medication for 30 to 40 days. Tests were then repeated <10 days before and approximately 30 days after the discontinuation of study medication. After a mean treatment duration of 31 days, there were no differences between the groups for any of the pulmonary function parameters. At the end of treatment (mean 211 days) and after the discontinuation of study medication (mean 32 days after the last dose), there was also no evidence of a change in pulmonary function in either group. For example, forced expiratory volume in 1 second values before β2 agonist inhalation in the ticagrelor and clopidogrel groups were 2.81 ± 0.73 and 2.70 ± 0.84 L, respectively, at the first visit and did not change significantly at subsequent visits. In conclusion, no effect of ticagrelor on pulmonary function was seen in this cohort of patients with acute coronary syndromes compared to clopidogrel.
Gesehen am 24.10.2022